The Active Role of Farmer Groups in Improving the Economy of Dam Village Communities - Agung Ilham Gumelar; Ratna Sari Dewi; Qotrun Nida (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Technological developments have triggered changes in the way we carry out economic activities. This change is closely related to ideas, creativity, innovation and speed that most of our farmers fail to understand and follow. As a result, farmers always get the smallest profit and are left behind in the economic chain. This study aims to find out and describe how the Bendungan Village Farmers Association provides counseling on the development of agricultural technology in Bendungan Village, to find out and describe how farmers respond to ideas and innovate to increase their agricultural yields and to find out and describe the obstacles the Bendungan Village Farmers Group Association has in improving The Economy of the Bendungan Village Community. This study used a descriptive qualitative method involving the Association of Farmers’ Group Management and Members of the Farmers’ Group in Bendungan Village. The data collected is then analyzed and reduced so that it can be presented in descriptive paragraphs. This study found the following results: 1) Bendungan Village Gapoktan used 3 counseling methods, namely scheduled counseling and incidental counseling. 2) Not all Farmer Groups and their members are ready and follow the ideas and innovations initiated by Gapoktan through counseling. 3) The Combined Farmers Group experienced difficulties in conveying (communicating) their ideas and ideas to stakeholders and farmers in Bendungan Village.